Catherine Drinker Bowen papers - Bowen, Catherine Drinker, 1897-1973.
Family and general correspondence; drafts of speeches, writings, and articles; literary manuscripts; research notes; publication production materials; clippings; scrapbooks; printed matter; and other papers relating primarily to Bowen's writings, especially her biographies of John Adams, Francis Bacon, Sir Edward Coke, Benjamin Franklin, and Oliver Wendell Holmes, and her study of the Constitutional Convention of 1787. Other topics include the Drinker family and the Bread Loaf Writers' Conference of Middlebury College, Vt. Correspondents include Julian P. Boyd, John Ciardi, Henry Steele Commager, Norman Cousins, Bernard Augustine De Voto, Felix Frankfurter, Hubert H. Humphrey, Lady Bird Johnson, Archibald MacLeish, Richard M. Nixon, Harold Ober, Ezra Pound, J.H. Powell, James Reston, Barbara Rex, Arthur M. Schlesinger, Jr., Barbara Wertheim Tuchman, Earl Warren, and Edward Weeks.
Library of Congress Prints and Photographs Division.
Author and biographer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, John, -- 1735-1826.; Bacon, Francis, -- 1561-1626.; Boyd, Julian P. -- 1903-1980 -- Correspondence; Ciardi, John, -- 1916-1986 -- Correspondence; Coke, Edward, -- Sir, -- 1552-1634.; Commager, Henry Steele, -- 1902-1998 -- Correspondence; Cousins, Norman -- Correspondence; De Voto, Bernard Augustine, -- 1897-1955 -- Correspondence; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Franklin, Benjamin, -- 1706-1790.; Holmes, Oliver Wendell, -- 1841-1935.; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Johnson, Lady Bird, -- 1912-2007 -- Correspondence; MacLeish, Archibald, -- 1892-1982 -- Correspondence; Nixon, Richard M. -- 1913-1994 -- Correspondence; Ober, Harold, -- 1881-1959 -- Correspondence; Pound, Ezra, -- 1885-1972 -- Correspondence; Powell, J. H. -- 1914-1971 -- Correspondence; Reston, James, -- 1909-1995 -- Correspondence; Rex, Barbara -- Correspondence; Schlesinger, Arthur M. -- 1917-2007 -- Correspondence; Tuchman, Barbara Wertheim -- Correspondence; Warren, Earl, -- 1891-1974 -- Correspondence; Weeks, Edward, -- 1898-1989 -- Correspondence; Drinker family; Drinker family -- Correspondence; United States. -- Constitutional Convention -- (1787); Bread Loaf Writers' Conference of Middlebury College; Authors, American -- Conferences -- Vermont; Biography; Authors; Biographers